UNA REVISIÓN DE LAS PERIODIZACIONES ARCHIVÍSTICAS DE LA EDAD MODERNA ESPAÑOLA - Zozaya Montes, Leonor (Documenta & Instrumenta - Documenta et Instrumenta, 2008)
The History of the municipal archives of the Hispanic Kingdoms has been insufficiently studied. Due to this a number of problems arise. One of these problems is the periodisation of archivism in the Modern Age, to which specialists have given an excessive role to the socalled State Archive theory, a hypothesis imported from Europe which cannot be adapted to Hispanic reality. These periodisations should take into account laws dictated by the kings to enforce the creation of Town Hall archives everywhere in the realm, and their consequences.